2010
DOI: 10.1177/0310057x1003800523
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Bilateral Superior Laryngeal Nerve Block to Aid Awake Endotracheal Intubation in a Patient with Cervical Spine Disease for Emergency Surgery

Abstract: Ultrasound has been widely used to locate nerves for various nerve blocks. The potential advantages of using ultrasound imaging for nerve blocks include reduction in the amount of local anaesthetic required, improved success rate, reduced time to perform the block and reduced complication rate. We describe the successful performance of ultrasound-guided bilateral superior laryngeal nerve block to facilitate awake fibreoptic intubation in a patient presenting for emergency surgery on the cervical spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Visualization of the superior laryngeal artery was inconsistent and difficult, despite an earlier case report suggesting the use of this landmark in finding the superior laryngeal nerve. 8 The hyoid bone, thyrohyoid cartilage, thyrohyoid membrane, and superior laryngeal nerve were visible in 40/40 scans (95% confidence interval, 0.896-1.0). 2 In this case series, we were able to obtain consistent reliable images of the superior laryngeal nerve as a hypoechoic structure and trace it as it perforated the thyrohyoid membrane.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Visualization of the superior laryngeal artery was inconsistent and difficult, despite an earlier case report suggesting the use of this landmark in finding the superior laryngeal nerve. 8 The hyoid bone, thyrohyoid cartilage, thyrohyoid membrane, and superior laryngeal nerve were visible in 40/40 scans (95% confidence interval, 0.896-1.0). 2 In this case series, we were able to obtain consistent reliable images of the superior laryngeal nerve as a hypoechoic structure and trace it as it perforated the thyrohyoid membrane.…”
Section: Discussionmentioning
confidence: 98%
“…However, ultrasound visualization of the superior laryngeal nerve was not always possible and ultrasound was essentially used to place local anesthetic in the approximate vicinity of the superior laryngeal nerve near the hyoid bone or perform a translaryngeal instillation of local anesthetic. [7][8][9] In cadavers, it is possible to simulate ultrasound-guided superior laryngeal nerve blockade and demonstrate dye placement around the nerve by placing the injectate either near the hyoid bone or directly onto the nerve. [8][9][10] Consistent sonographic visualization of the superior laryngeal nerve in patients however continues to be a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local anaesthetic agent was injected near the superior laryngeal artery after negative aspiration of blood, following which awake intubation was performed without complications. [8] However, it has been reported that there exist wide variations in origin of superior thyroid artery and its branch, the superior laryngeal artery. [9]…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ultrasound (USG)-guided approach has been used, wherein the probe is placed in a longitudinal plane. [1] Here, we describe a method in which we have placed the transducer transversely and achieved the nerve blockade successfully.…”
mentioning
confidence: 99%